A Farmer-based fruit seedling supply system in Dale Pilot Learning Woreda (PLW): experiences from IPMS - Yilma, K.; Berhe, Kahsay; Gebremedhin, Berhanu; Hoekstra, Dirk; Ayele, D.; Gebrehawariat, K. (International Livestock Research Institute, 2010)
Dale Woreda is well known for its avocado (Persia americana) and to a lesser extent mango (Mangifera indica) production. These fruit trees are planted along with coffee (Coffee arabica), enset (Enset ventricosum) and other crops. They are important sources of income and food, playing a considerable role in the livelihood of thousands of smallholder farmers of Dale. However, the varieties found in the area have large canopies that reduce land availability for other crops. They are also tall (10-15 m) thus harvesting becomes a challenge, particularly for women. Market prices for these varieties are low and during collection, there is considerable fruit loss when they fall, causing cracks and bruises and hence their rejection. The trees also take 7- 10 years to bear fruit and farmers mention that the land can be used more productively and therefore want to replace fruit trees with other more profitable crops. The diagnostic survey carried out by Improving Productivity and Marketing Success (IPMS) of Ethiopian farmers’ project identified some of the above production constraints as the major area of intervention. Further study was conducted by the International Centre for Research on Agro Forestry (ICRAF) which confirmed the above problems and suggested introduction of improved variety through grafting as one of the best solution to improve the quality of seed, reduce size and height as well as improve productivity and marketability of these varieties. Taking the experience of Dale for coffee seedling production where farmer’s nurseries have taken over 95% of seedling production, the Dale partners decided to use farmers’ nurseries as the base to start production of grafted seedlings. Using participatory extension methods with the help of various partners, the number of private nursery operators increased from the initial six (3 females) to 20 (7 female) in 2009. The number of seedlings produced has now reached 12,000 annually and this can be easily expanded since scions can now be obtained from mother trees established earlier in each of the nursery sites. Currently, seedlings are sold at around Birr 15/seedling to neighboring farmers, some on credit provided by the nursery operators. Linkages with the Productive Safety Net program are made to facilitate the scaling out of the sale of seedlings to emerging commercial farmers. Nursery operators earned between Birr 4,000–7,000 per year from these operations. Further skills development can still be made to improve survival rates of grafted seedlings. Attention will also need to be paid to the marketing of these improved varieties as well as the development of a responsive support system providing fresh knowledge, building capacity and new technologies.